Improving Speaking Participation Through Think-Pair-Share in an EFL Classroom - Akhmad Ghifari Ghifari; Muhammad Syahriwan; Naufal Fahreza; Abdul Syahid (DAS Institute, 2026)
Speaking participation is a persistent challenge in English as a Foreign Language (EFL) classrooms, particularly at the elementary school level where learners often experience anxiety and low confidence. This study aims to examine the effectiveness of the Think-Pair-Share (TPS) technique in improving students’ participation in speaking activities. The research employed a Classroom Action Research (CAR) design consisting of one cycle: planning, action, observation, and reflection. The participants were 25 sixth-grade students at a public Islamic elementary school in Palangka Raya, Indonesia. Data were collected through classroom observations, field notes, and informal interviews with the English teacher. The results indicate a substantial increase in students’ speaking participation after the implementation of TPS. Active participation rose from approximately 20-25% in the initial condition to more than 65–70% by the end of the action cycle. Students also demonstrated higher confidence and willingness to express ideas in English. These findings suggest that TPS provides a supportive and structured learning environment that reduces anxiety and encourages equitable participation. Therefore, TPS can be considered an effective and practical cooperative learning strategy for enhancing speaking participation in elementary EFL classrooms.